Evaluating the customer experience in Worten Resolve’s after sales repair service and its impact on satisfaction and word-of-mouth - Acabado, Ana Rita Sanchez Gonzalez (2022)
Given the increasing number of competitors in different sectors, it is essential for a company to differentiate from others by delivering to customers a memorable experience through its services. As such, it is imperative that companies evaluate their services to improve the relationship between the company and the customer, maximizing the level of customer experience, satisfaction, and promoting dissemination of a good experience. Henceforth, the aim of this research is to evaluate the customer experience at the Worten Resolve after sales repair service and its impact on customer satisfaction and word-of-mouth. Therefore, a quantitative study was carried out by applying a questionnaire to 154 customers of the stores considered for the study (Colombo and Vasco da Gama). The data analysis combined descriptive analysis, reliability analysis and mediation analysis, using simple and multiple linear regression. In addition, a qualitative study was also conducted by interviewing the supervisor of those stores. The results obtained, in the customer questionnaire and in the interview, are positive, showing that most customers are satisfied with the Worten Resolve repair service and that there is agreement between the customer's perspective and the service provider's perspective in most of the topics covered. By using hypotheses testing it was possible to conclude that, in this study, customer experience has a positive impact on customer satisfaction and on word-of-mouth. Finally, improvement opportunities for future studies are presented, such as increasing the number of stores analysed and in different regions of the country, as well as comparing them with competitor services.